Previous lower segment caesarean section -a potential risk factor for Placenta Previa - Rose S, Arul Anne; Gopalan, Ushadevi (International Journal of Medical Research and Review, 2015)
Introduction: Obstetrical hemorrhage continues to be an important cause of maternal mortality, accounting for 15-20% of maternal deaths. Placenta previa is an important cause of both antepartum and post partum haemorrhage. Aim of the Study: To determine the risk of subsequent occurrence of placenta previa in women with history of previous Lower Segment Caesarean Section (LSCS). Materials And Methods: The study was a hospital based prospective study conducted in our medical college and teaching hospital over a period of two years (2011-2013). A detailed history has been taken as per proforma for all pregnant women at or after 32 weeks who attended the hospital in the study period. As per inclusion and exclusion criteria of our study, study population has been selected. The study population was divided into control group [patients with unscarred uterus] and study group [patients with previous LSCS]. Placental location was done by Trans Abdominal Sonography- Ultrasound Sonogram (TAS-USS) and patients with placenta previa were followed up regularly till the time of delivery for pregnancy outcomes. Results: The incidence of placenta previa in patients without previous LSCS was 0.55% and in those patients with previous LSCS was 1.59%. It is statistically significant by Chi Square test X=4.39(P <0.05). Considering the relative risk (RR), in women with previous LSCS scar, the risk for developing placenta previa in subsequent pregnancy is three times more than women without LSCS scar. Conclusion: There is a strong association between previous LSCS and risk of subsequent development of placenta previa. The study also reinforces the importance of advocating vaginal delivery as far as possible and reduces the number of LSCS and future placenta previa.